1997
DOI: 10.1055/s-0038-1665428
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Prothrombin Gene Variant (nt20210A) in Venous Thrombosis and Arterial Disease

Abstract: SummaryThe prothrombin gene variant resulting form a G→A transition at position 20210 has been described as a common genetic risk factor for venous thrombosis. However, the risk for developing arterial disease is unknown. In this investigation, we studied 116 patients with venous thrombosis and 71 with arterial disease, all of whom were compared with 295 controls. Additionally, we also investigated the distribution of the prothrombin alleles among African descendents and Amazonian Indians from Brazil. The prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
1
14

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(131 citation statements)
references
References 15 publications
7
109
1
14
Order By: Relevance
“…Several studies confirmed this initial observation both in venous thrombosis and arterial disease [30,32].…”
Section: Introductionsupporting
confidence: 55%
“…Several studies confirmed this initial observation both in venous thrombosis and arterial disease [30,32].…”
Section: Introductionsupporting
confidence: 55%
“…Both these abnormalities are commonly found in patients with venous thromboembolism, with prevalences varying between 20% and 50% for factor V Leiden (Griffin et al, 1993;Koster et al, 1993;Svensson & Dahlba Èck, 1994) and between 5% and 19% for the prothrombin gene mutation (Poort et al, 1996;Arruda et al, 1997;Brown et al, 1997;Hillarp et al, 1997;Kapur et al, 1997;Cattaneo et al, 1998;Leroyer et al, 1998;Margaglione et al, 1998), depending on the criteria used for patients' selection. Their frequency in general populations of Caucasian origin varies from 1% to 7% for factor V Leiden (Rees et al, 1995) and from 1% to 5% for the prothrombin gene mutation (Rosendaal et al, 1998).…”
mentioning
confidence: 99%
“…The association of factor II G20210A mutation with an increased risk of venous thrombosis was reported by Poort et al [16]. Several studies confirmed this initial observation [17,18]. The patients with this genetic change show increased prothrombin levels and therefore more thrombotic activity [19].…”
Section: Other Genes In Coagulation Cascadementioning
confidence: 67%